Towards indicating human skin state in vivo using geometry-dependent spectroscopic contrast imaging - Ni, Guangming (2022)
Skin plays a significant role in human body function and its collagen states change during the human skin ageing process, which affects skin function. We previously reported on geometry-dependent spectroscopic contrast achieved by spectroscopic micro-optical coherence tomography (SμOCT), which discovered that transversely oriented and regularly arranged nano-cylinders selectively backscatter the long-wavelength lights and generate spectral centroid (SC) shifts towards the long wavelengths within a spectral window of 700 - 950 nm. Here we further proposed a novel method towards indicating the state of human skin in vivo using geometry-dependent spectroscopic contrast imaging. The proposed method can obtain spectroscopic contrast images of different human skin layers, including the papillary dermis and reticular dermis, and provide a quantitative method towards indicating collagen state in human skin in vivo. Experimental results have shown that the proposed method may potentially have the ability to assess the state of human skin.